SYNTHESIS OF TWO NOVEL DERIVATIVES OF CYCLOSPORIN A AND EVALUATION OF THEIR ANTIPROLIFERATIVE EFFECT ON CANCER CELL LINES - Ahmed Z. Abdelazem; Lee, So Ha (Assiut University, 2022)
Two novel derivatives of cyclosporin A were designed and synthesized. Synthesis of target compounds has been performed using olefin metathesis chemistry. The structures of target compounds were confirmed using 1H and 13C NMR and high-resolution mass spectroscopy. The in vitro antiproliferative effect of the two compounds was tested over NCI-60 cancer cell lines of nine different cancer types. The piperidinedione derivative (compound 7) had an inhibitory effect higher than 80% over 13 cancer cell lines, and close to or higher than 100% over six cancer cell lines. Compound 7 showed also significantly higher inhibitory activity than cyclosporin A against non-small cell lung cancer NCI-H226 cell line. Moreover, compound 7 showed an overall moderate antiproliferative activity against the NCI-60 cancer cell lines with a mean value of 57.54 %. While, the pyrrolidindione derivative (compound 6) showed weak antiproliferative activity against the NCI-60 cancer cell lines with a mean value of 28.83%. Finally, the predicted pharmacokinetic properties of compounds 6 and 7 were better than that of cyclosporine A.